Quantifying hydrothermal ammonium mobilization from sediment and implications for the marine biosphere: a case study from the Guaymas Basin, Gulf of California - Nathan Rochelle-Bates; Annabel Long; Graeme A. MacGilchrist; Andreas Teske; Eva E. Stüeken (Frontiers in Microbiology, 2025)
Fluid-rock interactions in hydrothermal systems are capable of liberating ammonium (NH4+) from sedimentary organic material and making it bioavailable for benthic and pelagic microbial communities. Hydrothermal systems in organic-rich sedimentary basins are therefore thought to have played a key role in supplying bioavailable nitrogen to the early biosphere. To place new quantitative bounds on this process, we examined sediments from active hydrothermal systems in the Guaymas Basin, a young oceanic spreading center in the Gulf of California. We analysed four shallow sediment cores that were taken in the Guaymas Basin’s hydrothermally-active Southern Trough. We used a combination of isotopic tracers (δ15N, δ13C) and elemental abundances to explore nitrogen and metal mobility in buried sediments. We found that ca. 54% of the organically-bound nitrogen is remobilized by active seepage in the top 10 cm of the sediment package within as little as 27–83 yr. Extrapolating these findings over the hydrothermally-active area of the basin yields an ammonium seepage flux of ca. 1.3–4.1 mol/s. In addition, high temperature venting liberates ca. 156–187 mol/s, as estimated from previous data. Assuming biological uptake of hydrothermally recycled ammonium in the water column, these fluxes could support up to 1.3% and 58% of export productivity, respectively. Our data also reveal that the accumulation of micronutrients or potentially toxic metals is influenced by the presence of organic material in seep sediments. The Guaymas case study demonstrates that hydrothermal seepage in sedimentary basins can create a significant nutrient flux and is an efficient means of recycling nutrients from organic matter at shallow burial depths. Hydrothermal nutrient fluxes could therefore have enhanced microbial activity in Earth’s history, in particular during time intervals when Earth’s oceans are thought to have been nutrient-depleted. Our data also highlight the role of organic material in enhancing metal mobilization and accumulation in otherwise metal-starved hydrothermal seeps.